BICYCLE ROTOR (International Journal of Engineering Sciences & Management Research, 2017)
Nowadays in agricultural sector, new techniques are invented to improve farming methods & outputs. For plantation of secondary crop where tractor operated rotor cannot be used due to insufficiency of space, a manually operated compact rotor is a need of the hour. While researching about project, we realized that, a compact model of can be rotated using a combination of gear & chain arrangement, thereby reducing equipment cost & improving work efficiency for secondary crop. This bicycle rotor is used in agriculture purpose, like to remove unwanted grass from farm, harrowing of soil.